Synthesis and biological activity of a potent optically pure autoinducer-2 quorum sensing agonist - Ascenso, Osvaldo S. (2021)
Quorum sensing (QS) regulates population-dependent bacterial behaviours, such as toxin production, biofilm formation and virulence. Autoinducer-2 (AI-2) is to date the only signalling molecule known to foster inter-species bacterial communication across distantly related bacterial species. In this work, the synthesis of pure enantiomers of C4-propoxy-HPD and C4-ethoxy-HPD, known AI-2 analogues, has been developed. The optimised synthesis is efficient, reproducible and short. The (4S) enantiomer of C4-propoxy-HPD was the most active compound being approximately twice as efficient as (4S)-DPD and ten-times more potent than the (4R) enantiomer. Additionally, the specificity of this analogue to bacteria with LuxP receptors makes it a good candidate for clinical applications, because it is not susceptible to scavenging by LsrB-containing bacteria that degrade the natural AI-2. All in all, this study provides a new brief and effective synthesis of isomerically pure analogues for QS modulation that include the most active AI-2 agonist described so far.